A systematic review of biomarkers among hospitalized patients with COVID‐19 predictive of venous thromboembolism: A communication from the Predictive and Diagnostic Variables Scientific and Standardization Committee of the ISTH. Issue 6 (26th August 2022) - Woller, Scott C.; de Wit, Kerstin; Robert‐Ebadi, Helia; Masias, Camila; Klok, Frederikus A.; den Exter, Paul L.; Morange, Pierre‐Emmanuel; Castelli, David; Hansen, John‐Bjarne
Abstract: Background: Thrombosis is reported to occur more often among patients with COVID‐19 than otherwise expected in the setting of viral pneumonia and sepsis. Systemic inflammatory biomarkers may be associated with venous thromboembolism (VTE) risk. The ISTH subcommittee on Predictive and Diagnostic Variables in Thrombotic Disease aimed to report the evidence on prognostic biomarkers for VTE in hospitalized patients with COVID‐19. Methods: Using a standardized Preferred Reporting Items for Systematic Reviews and Meta‐analysis methodology, we conducted a systematic literature review to identify studies reporting prognostic biomarkers for VTE among hospitalized patients with COVID‐19. Eligible studies included adults hospitalized with COVID‐19 and reported the prognostic associations between any biomarker measured on admission, and the subsequent diagnosis of deep vein thrombosis or pulmonary embolism. Two authors reviewed titles and abstracts, and three authors extracted study data and performed review of bias. Results were displayed descriptively. Meta‐analysis was not possible. Results: From the initial 196 identified studies, full‐text review was performed for 72 studies. Admission D‐dimer levels were associated with VTE during hospitalization in five studies, and elevated platelet count was associated with VTE during hospitalization in one study. The risk of bias ranged from low to high for included studies. Overall, there was a paucity of high‐quality prognostic studies. Studies on other biomarkers did not meet the systematic review inclusion criteria. Conclusions: Admission D‐dimer was associated with VTE diagnosis during hospitalization for COVID‐19; however, prospective validation of this finding is needed to identify optimal D‐dimer thresholds to guide VTE prophylaxis measures.